Reliability and optimization of structural systems : proceedings of the 11th IFIP WG7.5 Working Conference, Banff Canada, 2-5 November 2003 /: proceedings of the 11th IFIP WG7.5 Working Conference, Banff Canada, 2-5 November 2003. (2020) - Maes, Marc
No abstract available